Pelatihan Penyusunan Profil Usaha dan Proposal Pembiayaan Bagi Umkm - Muhammad Subardin; Muhammad Teguh; Gustriani Gustriani; Imelda Imelda; Harunurrasyid Harunurrasyid (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Lack of capital is a major problem faced by business, especially micro small medium enterprises (MSME) segment. One of the ways to get capital is applying loan to financial institutions, mainly the banking industry. However, in the credit application process due to lack of information, most small and micro businesses have difficulties in preparing business proposals that are in accordance with banking standards. Therefore, the Service Team and the Economics and Business Application Laboratory of the Economics Faculty carry out community service activities. It performed with models and methods of mentoring and empowerment for micro and small businesses regarding writing business profiles and proposals for credit applications. There are at least 34 entrepreneurs in Ilir Barat II Sub-district South Sumatera Province who participated in this activity and were assisted in making company profiles as well as business proposals. The evaluation results showed an increase in understanding of how to make business profiles and proposals by 80.06 percent of participants.